Synthesis of zephycandidine A from haemanthamine. Issue 16 (16th April 2020) - Murphy, Patrick J.; Tibble-Howlings, Jamie; Kowalczyk, Radoslaw M.; Stevens, Kevin
Graphical abstract: Highlights: The first reported synthesis of the alkaloid Zephycandidine A. A naturally occurring imidazo[1, 2- f ]phenanthridine alkaloid. Zephycandidine A Prepared in three steps from the naturally occurring alkaloid haemanthamine. Abstract: Zephycandidine A the first naturally occurring imidazo[1, 2– f ]phenanthridine alkaloid, isolated from Zephyranthes candida ( Amaryllidaceae ) has been prepared in three steps from the naturally occurring alkaloid haemanthamine.